+0  
 
-1
16
1
avatar+0 

PLEASE EXPLAIN

 Feb 15, 2024
 #1
avatar+129742 
+1

We have the form

 

y =  A cos  (B (x - D)) + C

 

A = the amplitude =   [ 3 - - 11] / 2 =  14 / 2 =  7

 

C= the midline =  [ 3 - 11 ] / 2 =   -8 / 2 =   -4

 

The period  =  [ ((5/2)pi + 2 pi)) / 2    - pi/4 ] =   [ (10/4)pi + (8/4)pi ) / 2   - pi/4]  = 

[ (18/4)pi / 2 - pi/ 4] =  [ (18/8)pi - pi/4 ]  = [ (9/4)pi - pi/4 ] = (8/4)pi  = 2pi

 

B =  2pi / period =  2pi / 2pi  = 1

 

D = the phase shift = pi/4 

 

 

The equation is

 

y = 7cos ( x  - pi/4) - 4

 

See here  :

 

 

 

 

cool cool cool

 Feb 15, 2024

7 Online Users

avatar
avatar
avatar
avatar
avatar
avatar